Atrial fibrillation activation patterns predict freedom from arrhythmias after catheter ablation: utility of ExTRa mapping™ - Aoyama, Daisetsu; Miyazaki, Shinsuke; Hasegawa, Kanae; Nomura, Ryohei; Kakehashi, Shota; Mukai, Moe; Miyoshi, Machiko; Yamaguchi, Junya; Sato, Yusuke; Shiomi, Yuichiro; Ikeda, Hiroyuki; Ishida, Kentaro; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background Mechanisms underlying atrial fibrillation (AF) are widely complex and vary tremendously among individuals. Objectives This retrospective study aimed to investigate the association between AF activation patterns and clinical outcomes post-ablation. Methods Fifty-five AF patients (64.0 ± 12.9 years; 41 men; 17 paroxysmal) underwent bi-atrial endocardial driver mapping during AF pre-ablation with a real-time phase mapping system (ExTRa Mapping). The nonpassively activated ratio (%NP) of meandering rotors and multiple wavelets relative to the recording time was evaluated in 26 atrial segments [15 in the left atrium (LA) and 11 in the right atrium]. Irrespective of the mapping results, all patients underwent standard AF ablation via cryoballoons and/or radiofrequency catheters. Results In a median follow-up interval of 27(14–30) months, 69.1% of patients were free from recurrent arrhythmias and antiarrhythmic drugs at one year post-procedure. Patients with recurrent AF were more likely to have non-paroxysmal AF, a significantly larger LA size, and higher LA maximal %NP(LAmax%NP) and LA anterior wall %NP(LAAW%NP) than those without recurrent AF. A multivariate Cox regression analysis showed that both an LAmax%NP (hazard ratio [HR] = 1.075; 95% confidence interval [CI] = 1.02–1.14, p = 0.012) and LAAW%NP (HR = 1.061; 95% CI = 1.01–1.11, p = 0.013) were independent predictors of atrial arrhythmia recurrence. The optimal cutoff points for the LAmax%NP and LAAW%NP for predicting AF recurrence were 64.5% and 60.0%, respectively. A Kaplan-Meier analysis demonstrated that both an LAmax%NP > 64.5% (p = 0.0062) and LAAW%NP > 60.0% (p = 0.014) were associated with more frequent AF recurrences. Conclusion Baseline AF activation pattern mapping may aid in predicting freedom from arrhythmias after standard AF ablation procedures.